The Spatial Expression of Informal Livelihoods: An Examination of Charcoal Production in Tondo, Manila and Resettlement - Sicam, Olivia Alma G. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 8, 2022)
Access and provisions for livelihood are mandated by policies in housing resettlement. However, while the design and planning of housing developments typically focus on the particulars of housing units, little attention is given to the spatial details of livelihood reconstruction. The study addresses this issue by examining Ulingan, an informal settlement engaged in the communal production of charcoal, clarifying its spatial organization, and comparing it with St. Martha Estate Housing, the resettlement site. By examining charcoal-making in Ulingan and its spatial characteristics, the research sheds light on the organization of space in communal livelihoods within informal human settlements and highlights how it compares with socialized housing templates. The study suggests that, although spatial organization influences the cultivation of systems of cooperation in livelihoods, it is also important to consider the broader context in which informal livelihoods thrive. Future studies should examine the impact of spatial organization in different types of resettlement sites (e.g., in-city, off-city, slum upgrading) across various types of informal economies to inform planning for livelihood reconstruction.